(untitled) (Research, Society and Development, 2021)
This article aims to analyze the institutes of the appropriate means of conflict resolution provided for in the Code of Civil Procedure 2015, especially arbitration. Through a technical approach, it is intended to demonstrate that arbitration has existed in the legal system since 1996, but only with the advent of the new Code of Civil Procedure has become more relevant adoption of the institute. Its applicability is verified in complex cases, besides demonstrating its importance with regard to the scope of social pacification because it is a method of heterocomposition of conflicts, in order to analyze the benefits of its use and its efficiency applied to the specific case. It analyses the issue of the full arbitration clause and the empty arbitration clause and its differences is addressed. It is also aimed at studying the appropriate means of resolving conflicts in the face of social problems today and their importance with regard to the contribution to a reduction of processes within the judiciary. It was opted for the deductive methodology based on bibliographic research through doctrine as well as infraconstitutional legislation.